1712 'Less contented as a person': preliminary data from the lgi1-qol study. (1st December 2017) - Binks, Sophie NM; Jacob, Saiju; Maddison, Paul; Coebergh, Jan; Isabel Leite, M; Irani, Sarosh R
Abstract : Objective: To describe the long-term cognitive, neuropsychiatric and quality of life (QOL) outcomes in LGI1-antibody encephalitis. Methods: 42 patients, forming the initial cohort of the LGI1-QoL study, have undergone detailed evaluation. Preliminary results of the Addenbrooke's Cognitive Examination – Revised (ACE-R), Hospital Anxiety and Depression Scale (HADS), EQ-5D-5L and Life Satisfaction Questionnaire (LSQ) are presented. Results: Patients (29 male) aged 44–86 were assessed at a median of four years post-illness onset (range 0.5–15 years). Mean ACE-R was 90 (range 68–99); there were no differences with length of follow-up. Depression or anxiety (HADS >7) were found in 15% and 28% respectively, with a modest tendency to improve over time. Subjective patient health ratings, via the EQ-5D-5L, were worse post than pre-illness, most marked at younger ages, while the LSQ showed significant decline in the domains of life as a whole, leisure, vocation, sexual life and contacts with friends, with the most significant change (p=<0.0001) in vocation and, surprisingly, sexual life. The localisation of the sexual dysfunction was explored with imaging and immunohistochemical studies suggesting localisation to the amygdala. Conclusions: There are notable effects on health and QOL several years post-LGI1-antibody encephalitis. Future work should focus on early interventions to improve outcomes.